Demand Driven MRP – The need to standardise an implementation process. - A. Orue; A. Lizarralde; A. Kortabarria (International Journal of Production Management and Engineering, 2020)
Since the creation of the demand-driven material requirement planning (DDMRP) model, numerous studies have analysed the methodology’s significant impact on different organisations. Several successful cases and research studies into DDMRP have demonstrated that the methodology is beneficial to organisations because it increases their service level and stock adjustments; however, there is a dearth of literature regarding the steps necessary to implement this model successfully. This document delivers a systematic review of the literature based on the work done by Kitchenham (2004) with the aim of analysing studies that investigate the standardization of the process of implementing the model. Once the lack of research has been demonstrated, a possible line of future research can be outlined to standardise the implementation process of the DDMRP model to achieve its full potential.